Analysis of I-Generation Social Media Communication in Creating Brand Image Oof Demak Kota Wali Destinations - Anita Septiani Rosana; Saifudin Saifudin (UIN Salatiga, 2022)
This study investigates the factors of i-generation social media communication influencing destination brand image. This research examines the impact of e-WOM on social media on destination brand image. The sample data used in this study were 97 respondents from 4 provinces in Indonesia. Multiple linear regression was used to test the significance of the effect of the independent variable on the dependent variable. The IBM SPSS 25 test results show that e-WOM on social media can positively affect the destination brand image. Local governments can predict tourist behavior through this paper. As for academics, this paper can be used for further research by integrating social media communication as a predictor of destination brand image. Empirically this research helps to improve understanding of how the role of social media communication creates a brand image in a destination.